A rapid and reversible thermochromic supramolecular polymer hydrogel and its application in protected quick response codes. (23rd January 2020) - Li, Bo; Lin, Cuiling; Lu, Chenjie; Zhang, Jinjin; He, Tian; Qiu, Huayu; Yin, Shouchun
Abstract : A rapid and reversible thermochromic fluorescent supramolecular polymer hydrogel prepared by orthogonal self-assembly of host–guest and metal coordination interactions, has been used in protected quick response codes. Abstract : A rapid and reversible thermochromic fluorescent supramolecular polymer hydrogel was prepared via orthogonal self-assembly involving host–guest interactions and metal coordination interactions. This supramolecular polymer hydrogel exhibits responsiveness to multiple stimuli induced by competitive ligands and temperature, and excellent self-healing properties after being destroyed by external forces. Furthermore, the introduction of TPE units into the supramolecular hydrogel endows it with bright blue fluorescence, satisfying the demand for protected quick response (QR) codes with improved durability and security. A three-dimensional QR code was then constructed using this blue-light-emitting fluorescent supramolecular polymer hydrogel, which could hide information under natural light at high temperature or in the presence of competitive ligands, but display it under UV light irradiation at low temperature. Therefore, the QR code information is in a protected state and can only be read under specific conditions. Moreover, due to the dynamic reversibility of non-covalent interactions, the protected QR code also shows excellent self-healing performance after being destroyed.